Bifunctional Ag-Decorated CeO2 Nanorods Catalysts for Promoted Photodegradation of Methyl Orange and Photocatalytic Hydrogen Evolution - Jinwen Liu; Li Zhang; Yifei Sun; Yang Luo (Nanomaterials, 2021)
The photodegradation of organic pollutants and photocatalytic hydrogen generation from water by semiconductor catalysts are regarded as the of the most promising strategies to resolve the crisis of global environmental issues. Herein, we successfully designed and prepared a series of silver-decorated CeO2(Ag/CeO2) photocatalysts with different morphologies by a facile hydrothermal route. The physical properties, charge transfer behavior and photocatalytic performances (degradation and hydrogen evolution) over diverse catalysts with nanocubes, nanoparticles and nanorods shapes were comprehensively studied. It was found that the Ag-decorated CeO2 nanorods (Ag/R-CeO2) demonstrate the best activity for both photocatalytic methyl orange (MO) degradation and photocatalytic H2 production reaction with attractive stability during cycling tests, suggesting its desirable practical potential. The superior performance of Ag/R-CeO2 can be ascribed to (1) the facilitated light absorption due to enriched surface oxygen vacancies (OVs) and plasmonic Ag nanoparticles on nanorods, (2) the facilitated photo-excited charge carrier (e−-h+) separation efficiency on a metal/oxide hybrid structure and (3) the promoted formation of active reaction intermediates on surface-enriched Ag and oxygen vacancies reactive sites on Ag/CeO2 nanorods. This study provides a valuable discovery of the utilization of abundant solar energy for diverse catalytic processes.